The Apolipoprotein B/A1 Ratio is Associated With Metabolic Syndrome Components, Insulin Resistance, Androgen Hormones, and Liver Enzymes in Women With Polycystic Ovary Syndrome - He, Hui; Feng, Jiaxing; Zhang, Shike; Wang, Yu; Li, Jian; Gao, Jingshu; Cong, Jing; Gong, Yi; Wu, Xiaoke (Frontiers in Endocrinology, 2022)
Aim: To evaluate the relationship between Apolipoprotein B/Apolipoprotein A1 (ApoB/ApoA1) ratio and metabolic parameters including metabolic syndrome (Mets) components, insulin resistance (IR), androgen hormones, cardiac and liver enzymes at baseline of women with polycystic ovary syndrome (PCOS), and investigate whether ApoB/ApoA1 ratio is a useful predictor of MetS and IR. Methods: This was a secondary analysis of a randomized controlled clinical trial. Among 1000 PCOS women, 957 participants with available data of ApoB and ApoA1 were analyzed. We compared metabolic parameters across ApoB/ApoA1 quartiles, assessed the association between ApoB/ApoA1 ratio and these parameters as well as the risk of MetS and IR, and determined the predictive value of ApoB/ApoA1 ratio for identifying MetS and IR. Results: The analyses showed ApoB/ApoA1 ratio was positively associated with age, body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), lipoprotein, fasting plasma glucose (FPG), fasting insulin (FIN), homeostatic model assessment-insulin resistance (HOMA-IR), high free testosterone (FT), high free androgen index (FAI), lactate dehydrogenase (LDH), alanine transferase (ALT), aspartate transferase (AST), and higher prevalence of MetS and IR, but decrease in high-density lipoprotein (HDL), sex hormone-binding globulin (SHBG), and creatine kinade MB (CKMB). Linear regression showed ApoB/ApoA1 ratio was associated with WC, SBP, TC, TG, LDL, lipoprotein, FPG, FIN, HOMA-IR, FT, FAI, ALT and AST, while was negatively correlated with HDL and SHBG after adjustment for age and BMI. Logistic regression showed compared with ApoB/ApoA1 ratio in quartile 1, those in quartile 4 demonstrated a higher risk of MetS (OR: 24.15; 95%CI: 7.68-63.89) and IR (OR: 1.73; 95%CI: 1.07-2.80) after adjusting confounding factors. ROC curve analyses showed the AUC MetS was 0.84 (95%CI: 0.81-0.86), provided 86.8% sensitivity and 70.3% specificity with a threshold value of 0.64, and the AUC IR was 0.68 (95%CI: 0.64-0.71), provided 74.3% sensitivity and 58.2% specificity with a threshold value of 0.56. Conclusions: Our results suggest that increased ApoB/ApoA1 ratio is associated with progressively worse Mets components, IR, androgen hormones, and elevated liver enzymes, and can be utilized to predict MetS and IR in PCOS women.